Influence of Fine Metal Particles on Surface Discharge Characteristics of Outdoor Insulators - Yong Liu; Bowen Xia; Boxue Du; Masoud Farzaneh (Energies, 2016)
Focusing on the influence of fine metal particles on the insulation characteristics of outdoor insulators, spherical micrometer-level iron powders were used to represent fine metal particles of different parameters on a polymer insulator specimen surface. Dynamic movement and lift-off behavior of fine particles, as well as the triggered surface discharges under AC voltage were investigated in a uniform electric field under different experimental conditions. The results reveal that the inception, propagation and intensity of surface discharges are significantly affected by the particle parameters, including particle size, amount and distributing characteristic. Based on the measurement of light emission during the flashover process using a high-speed camera, the process of surface discharge to flashover triggered by the fine metal particles were investigated to obtain a relationship between flashover voltage, discharge light intensity and particle parameters. It is suggested that particle size smaller than 28 µm and particle amount more than 40 mg in contact with the non-uniform distribution can cause a significant distortion and intensification of the electric field resulting in a higher risk of surface discharges leading to flashover. Such investigations can enhance the operating reliability of outdoor insulators subjected to these conditions.